PERFORMANCE OF RAPPORTEURSHIPS IN THE RESEARCH ETHICS COMMITTEE (International Seven Journal of Multidisciplinary, 2025)
The research on the quantitative advancement of reports carried out by the members of the Research Ethics Committee of the Gaspar Vianna Hospital de Clínicas Foundation during the years 2020 until May 2024, allowed the projection of techniques aimed at advancing in the increase in productivity of the number of reports by the members. The investigation took place through an analysis of the increases in the number of reports in the aforementioned period. From the analysis, gradual increases in the number of rapporteurships were demonstrated. Having as possible triggering factors, the increase in incentive for scientific production, the encouragement of members for the greatest possible agility in carrying out the reports of the projects now submitted to the Committee, better distribution of projects to the 14 members of the Committee in the most equal way possible, in order not to cause overload to any of the members. Thus, supporting the data, in 2020 96 rapporteurships were carried out, in 2021 there were 124, 2022 there were 149, in 2023 there were 174 and from January to May 2024 they have already reached the level of 85 rapporteurships. In view of the above, it is possible to see that it is extremely important to observe this growth in the number of reports to our Committee, since this will have a favorable impact on the future achievement of the CEP/FHCGV accreditation. For the institution, this characteristic is of paramount importance, since it is a hospital with the mission of teaching, research and assistance. With the responsibility of training trained and ethically committed professionals.